Saving our planet - de la Bedoyere, Camilla; Wood, Steve (Essex, UK Miles Kelly, 2023)
Explore the wonderful planet we live on and learn how to make smart choices every day to help save it. Each page is packed with fantastic information, and the poster provides lots of ideas on how you can reduce, reuse and recycle
Includes a poster with helpful tips
Science (Environment)
Keywords: Environment